Os impactos socioambientais gerados na ocupação urbana do bairro Jardins- Aracaju-Sergipe - Santos, Marilda Colares Jardelina dos (2011)
The rapid rate of population growth, increasing urbanization coupled processes that are often disorderly, intensifying deforestation and causes the transformation of the natural environment, giving rise to questions about the depletion of natural resources. In this scenario, the housing boom has been one of the strongest factors of environmental degradation in several Brazilian cities. The urbanization process has compressed an ecosystem that is found in urban centers that are mangroves, reducing its surface and lose the natural quality of its waters by sewage effluent from dwellings, commercial establishments, industries and services, common in cities where the sewage does not meet the entire population. The Ecological Park Municipal Tramandaí inserted in this context of urban sprawl, was diagnosed as highly impacted by environmental tensioners, reduction of the mangrove and water pollution in this creek. Aiming to make an assessment of social impacts generated by the urban occupation in the neighborhood of the county Jardins, we applied a methodology based on the model PER (Pressure, State, Response), with the elaboration of an array of urban environment indicators. The application of this model relied on to contribute in building policies, planning and management that guide the development of sustainable levels. The process of planning and management of the natural and man-made, to promote sustainable development require continuous and dynamic performance. The characterization of the matrix indicators applied PER provided, according to the causes and agents, the understanding of the process of environmental degradation. The results revealed the complexity of the issues present in a process of management of the natural and man-made that enables the community and decision makers are aware of the socioeconomic and environmental features that are in the area.